TM-Polarization One-Dimensional Photonic Crystal Design - Elham Jasim Mohammad; Gaillan H. Abdullah (Institute of Advanced Engineering and Science, 2013)
A theoretical investigation of one dimensional planar photonic crystal is carried out. These photonic crystal consist of a dielectric layer structures with refractive index n1=1.45 and n2= 3.45. This work presents a systematic investigation of the reflection, forbidden bands and density of state of p-polarization. In optical sciences, the refractive index of an optical medium is a most fundamental quantity. The refractive index determines the refraction and reflection occurring at the boundary between two media. The propagation angle in one medium is taken with respect to normal inside the first medium varies between 0 and π/2. The program is written in MATLAB to simulate and analysis dispersions of electric magnetic waves in one dimension photonic crystal.